2015
DOI: 10.1161/circresaha.116.304668
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evaluation of Myocardial Viability and Stem Cell Engraftment Demonstrates Salvage of the Injured Myocardium

Abstract: Rationale The mechanism of functional restoration by stem cell therapy remains poorly understood. Novel manganese-enhanced MRI and bioluminescence reporter gene imaging (BLI) were applied to follow myocardial viability and cell engraftment, respectively. Human-placenta-derived amniotic mesenchymal stem cells (AMCs) demonstrate unique immunoregulatory and pre-cardiac properties. In this study, the restorative effects of three AMC-derived sub-populations were examined in a murine myocardial injury model: 1) unse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…Our MiCMs have shown to improve cardiac function of injured mouse hearts after MI. We observed that the MiCM-derived exosomes exhibited similar functions, such as cardiac-protective role, improving LVEF (left ventricular ejection fraction) and myocardial viability 106,107 . The exosomal cargo contained several up-regulated miRNAs, including miR-92a believed to stimulate endogenous anti-apoptotic, pro-angiogenic, and anti-fibrotic pathways.…”
Section: Therapeutic Effects Of Exosomes Derived From the Differenmentioning
confidence: 77%
“…Our MiCMs have shown to improve cardiac function of injured mouse hearts after MI. We observed that the MiCM-derived exosomes exhibited similar functions, such as cardiac-protective role, improving LVEF (left ventricular ejection fraction) and myocardial viability 106,107 . The exosomal cargo contained several up-regulated miRNAs, including miR-92a believed to stimulate endogenous anti-apoptotic, pro-angiogenic, and anti-fibrotic pathways.…”
Section: Therapeutic Effects Of Exosomes Derived From the Differenmentioning
confidence: 77%
“…None of the studies included reported safety end points such as “Major Cardiovascular Adverse Events” (MACE). In 22 of the 34 included groups, immunodeficient mice were used, yet tumor – more precisely teratoma – formation in animals receiving murine PSCs were reported in two of these groups only [21, 22]. …”
Section: Resultsmentioning
confidence: 99%
“…This approach uses autologous cells, thus avoiding alloimmune rejection. iPSC-derived cardiomyocytes from human placenta amniotic MSCs engrafted successfully in immunocompetent SVJ mice and improved myocardial viability and cardiac function after MI (77,78). These exosomes transported several upregulated miRNAs, including miR-92a which has been associated with antiapoptotic, proangiogenic, and antifibrotic effects.…”
Section: Cardioprotection By Exosomes From Ipsc-derived Cardiomyocytesmentioning
confidence: 99%